Cooperation - Tuomela, R. author. aut Link
XIII, 436 p.
Keywords: In Cooperation, A Philosophical Study, Tuomela offers the first comprehensive philosophical theory of cooperation. He builds on such notions a collective and joint goals, mutual beliefs, collective commitments, acting together and acting collectively. The book analyzes the varieties of cooperation, making use of the crucial distinction between group-mode and individual-mode cooperation. The former is based on collective goals and collective commitments, the latter on private goals and commitments. The book discusses the attitudes and the kinds of practical reasoning that cooperation requires and investigate some of the conditions under which cooperation is likely, rationally, to occur. It also shows some of the drawbacks of the standard game-theoretical treatments of cooperation and presents a survey of cooperation research in neighbouring fields. Readership: Essential reading for researchers and graduate students in philosophy. Also of interest to researchers int he social sciences and AI.